Needs Assessment in Postgraduate Medical Education:A Review - Dr. Savithiri Ratnapalan MRCP,FRCPC, (Medical Education Online, 2002)
Although the concept of needs assessment in continuing medical education is well ac-cepted, there is limited information on needs assessment in postgraduate medical education. We discuss the learning needs of postgraduate trainees and review the various methods of needs as-sessment such as: questionnaire surveys, interviews, focus groups, chart audits, chart-stimulated recall, standardized patients, and environmental scans in the context of post graduate medical edu-cation.